Analysis Of The Effectiveness Of Total Neoadjuvant Therapy In The Treatment Of Patients With Rectal Cancer - Saydamatov X.U (Zien Journals, 2025)
One of the major limitations of the traditional treatment sequence is that a substantial proportion of patients are unable to complete planned adjuvant chemotherapy. Postoperative complications, prolonged recovery, stoma-related issues, and decreased performance status frequently lead to dose reductions, treatment delays, or complete omission of systemic therapy.
Keywords: chemotherapy; reductions; treatment